2022
DOI: 10.3390/healthcare10122342
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Anxiety Levels in Latin American Immigrants as Caregivers of Older Adults in Spain

Abstract: Increased life expectancy in Spain has highlighted the need for formal caregivers who care for older adults who live at home. In many cases, families choose to hire immigrants from Latin America who, on many occasions, have been forced to emigrate, which causes a considerable psychological impact on them. To this, other factors such as precarious working conditions, loneliness, or high workload are added, which leads to many caregivers becoming sick. The aim of this study was to assess the quality of life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Insomnia 3. Depression 9 Fernández-Carrasco et al (2022) 32 Spain 1. WHOQOL-BREF quality of life assessment 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insomnia 3. Depression 9 Fernández-Carrasco et al (2022) 32 Spain 1. WHOQOL-BREF quality of life assessment 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that migrant women with high language proficiency have better emotional health, with lower levels of psychological well-being, acculturation stress, and anxiety, as they are less likely to feel lonely and better able to integrate into society. 24 , 25 , 29 , 30 , 32 This is because it affects acculturation stress and psychological well-being, 4 loneliness, 24 sadness and health, 28 mental health, 29 and emotions. 31 This is interpreted as empathy and interaction-based communication based on language skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the International Organization for Migration (IOM)’s World Migration Report published in 2020, there were estimated to be over 270 million international migrants in 2020, equivalent to about 3.5% of the world’s population. [26] In Türkiye, approximately 3.5 million Syrians primarily reside in border provinces, accounting for 3.73% of the country’s population. [27] Among Syrian migrants, 2.1% fall within the 65 years and older age group.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they must cope with cultural and economic challenges in adapting to the country they had to migrate to, including language barriers, limited access to healthcare, and psychosocial issues. [26,35] Studies have shown that all these challenges and problems faced by immigrants have a negative impact on their health and quality of life. [36] Therefore, it is essential to implement policies and interventions that mitigate the adverse effects of chronic diseases and psychological and social situations related to migration, allowing elderly immigrants to age healthily and independently.…”
Section: Introductionmentioning
confidence: 99%